Size control of metal nanoparticles : silver nanoprisms - Chiam, Kim Yeow. (2010)
Nanoparticles have been garnering much attention due to the unique properties that is absent when it exists in its bulk form. As such, different shapes and sizes of nanoparticles have been synthesized to date and these nanoparticles can be used in different types of applications, especially non-spherical colloidal nanoparticles. The sizes and shapes of these nanoparticles can be tuned and controlled via experimental parameters. Silver nanoprisms have been successfully formed by irradiating aqueous silver nanocolloids with visible light and the nanoprisms were characterized by UV-Vis and TEM. Results have shown that by varying the excitation wavelengths and the pH of the raw solution, the nanoprism sizes can be controlled.